Clash of powers : US-China rivalry in global trade governance - Hopewell, Kristen (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2020)
The US-China trade war instigated by President Trump has thrown the multilateral trading system into a crisis. Drawing on vast interview and documentary materials, Hopewell shows how US-China conflict had already paralyzed the system of international rules and institutions governing trade. The China Paradox - the fact that China is both a developing country and an economic powerhouse - creates significant challenges for global trade governance and rule-making. While China demands exemptions from global trade disciplines as a developing country, the US refuses to extend special treatment to its rival. The implications of this conflict extend far beyond trade, impeding pro-development and pro-environment reforms of the global trading system. As one of the first analyses of the implications of US-China rivalry for the governance of global trade, this book is crucial to our understanding of China's impact on the global trading system and on the liberal international economic order
Introduction -- The Doha Round impasse -- The new politics of agricultural subsidies : a US-China battle -- The dragon in the world's oceans : fisheries subsidies -- Beyond the WTO : erosion of the export credit arrangement -- Negotiating in the dragon's shadow : export credit for coal plants -- Conclusion
Title from publisher's bibliographic system (viewed on 29 Jan 2021)
Keywords: International trade -- Political aspects; Balance of power; Hegemony; Commercial policy